IMPLEMENTASI METAFORA KONSEPTUAL DALAM TERJEMAHAN KITAB SIMṬU AL‑DURAR, OLEH ‘ALĪ BIN ḤUSAIN AL-ḤABSYĪ - Syahbany, Ahmad; Kulsum, Umi; Abdullah, Abdullah; Ats Tsaqofi, Waki; Suparno, Darsita; Mubarak, Zacky (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
This study aims to analyze the application of conceptual metaphors in the Indonesian translation of Simṭu al-Durar by ‘Alī bin Ḥusain al-Ḥabsyī, using the conceptual metaphor theory of Lakoff and Johnson. Metaphors are viewed not merely as rhetorical ornaments but as conceptual frameworks that shape human understanding of reality. Employing a descriptive qualitative method, this research examined 23 metaphorical expressions from the translated text, classified into three categories: ontological, structural, and orientational metaphors. The results indicate that ontological metaphors dominate (15 data points), followed by structural metaphors (6 data) and orientational metaphors (2 data). These metaphors serve to clarify abstract concepts such as guidance, nobility, and spiritual journeys through concrete imagery like light, pearls, and paths. This study highlights the significance of understanding metaphors in translating religious texts, as metaphors not only beautify the language but also mediate the readers’ spiritual experience. The findings are expected to contribute theoretically to translation studies and provide practical guidelines for translators of religious texts.